The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10439-013-0840-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Strain on Solute Diffusion in Human TMJ Discs: An Electrical Conductivity Study

Abstract: This study investigated the effect of mechanical strain on solute diffusion in human TMJ discs (mean cadaver age 77.8) using the electrical conductivity method. The electrical conductivity, as well as small ion diffusivity, of male and female TMJ discs was determined under three compressive strains. In the male group, the average disc electrical conductivity (mean ± sd) at 0% strain was 5.14±0.97 mS/cm, decreased to 4.50±0.91 mS/cm (−12.3%) at 10% strain, and 3.93±0.81 mS/cm (−23.5%) at 20% compressive strain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…This is likely because meniscus composition is most like that of TMJ tissue, which also has a relatively low GAG content as compared to articular cartilage or intervertebral disc (Almarza and Athanasiou, 2004). The strain-dependent behavior of electrical conductivity and relative ion diffusivity found here is similar to results in the literature for other cartilaginous tissues (i.e., meniscus, articular cartilage, intervertebral disc, TMJ), which showed that static compression leads to reduced solute diffusivity and/or electrical conductivity Jackson et al, 2008;Kleinhans et al, 2015;Kuo et al, 2011;Quinn et al, 2000;Quinn et al, 2001;Wright et al, 2013;Yuan et al, 2009). This change is likely due to reduced tissue water content caused by fluid exudation during compression.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This is likely because meniscus composition is most like that of TMJ tissue, which also has a relatively low GAG content as compared to articular cartilage or intervertebral disc (Almarza and Athanasiou, 2004). The strain-dependent behavior of electrical conductivity and relative ion diffusivity found here is similar to results in the literature for other cartilaginous tissues (i.e., meniscus, articular cartilage, intervertebral disc, TMJ), which showed that static compression leads to reduced solute diffusivity and/or electrical conductivity Jackson et al, 2008;Kleinhans et al, 2015;Kuo et al, 2011;Quinn et al, 2000;Quinn et al, 2001;Wright et al, 2013;Yuan et al, 2009). This change is likely due to reduced tissue water content caused by fluid exudation during compression.…”
Section: Discussionsupporting
confidence: 85%
“…This value is the averaged relative diffusivity of Na þ and Cl À ions, which were assumed to carry the current as the primary ions in PBS solution (Kuo et al, 2011;Wright et al, 2013).…”
Section: Relative Ion Diffusivitymentioning
confidence: 99%
See 3 more Smart Citations